HISTORY TEACHER CREATIVITY IN INSTILLING STUDENT LEARNING MOTIVATION - Hamidah, Nur; Sari, Ulfi Andrian (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to determine the level of creativity of teachers in instilling historical motivation in Senior High School 1 Pacet. Students learning motivation, especially in history subjects at Senior High School 1 Pacet is low, students are lazy to read, rely too much on friends, use difficult language and also limited books make students lazy to study history. The creativity of teachers, especially in instilling learning motivation, is certainly needed so that students are enthusiastic in studying history. This research method uses descriptive qualitative methods by conducting observations, interviews, and also document. The interviewees were the history teacher of the one package system as well as students. The results of the research on teacher creativity in instilling learning motivation in students were carried out using various methods (assignment discussions, lectures, SQ3R, quizzes, question and answer), the use of various learning media (videos, pictures, whiteboards, and also Power Point), the use of teaching materials other than books (videos, modules, and internet), spontaneous questions and also working together with outsiders. The creativity of teachers in instilling learning motivation in history subjects at Senior High School 1 Pacet can be said to be good. Teachers seek many ways to motivate students to study history.